REPRESENTATIF KESANTUNAN TOKOH-TOKOH DALAM FILM THE FABULOUS UDIN KARYA RONS IRAWAN (REPRESENTATIVE CHARACTERISTICS OF CHARACTER IN THE FABULOUS UDIN FILM BY RONS IRAWAN) - Rahimah, Atiyat (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractRepresentative Characteristics of Character in the Fabulous Udin Film by Rons Irawan. This research aims to find out and understand politeness in language speech acts from the film The Fabulous Udin in order to be a role model for readers, because in the film there are many scenes and dialogues that are worth emulating. This research uses descriptive methods and a qualitative approach. The main data in this research are positive politeness and negative politeness found from the recording of the film The Fabulous Udin, while the supporting data is the synopsis of the film The Fabulous Udin. Representative politeness of the characters in the film The Fabulous Udin by Rons Irawan is divided into two, namely positive politeness and negative politeness. Positive and negative politeness acts are carried out by the characters in order to facilitate communication and maintain the speaker's self-esteem and the self-esteem of the interlocutor, so that a close relationship between the speaker and the interlocutor is established. Positive politeness in the film The Fabulous Udin is (1) paying attention to what the interlocutor needs, (2) using a form of group solidarity, (3) involving the interlocutor in the speaker's activities, (4) offering or promising something, (5) giving praise to the interlocutor, (6) avoiding inappropriateness and (7) being funny. The negative politeness found in the film The Fabulous Udin is (1) indirect expression, (2) being pessimistic, and (3) minimizing coercion. The dominant type of politeness is positive politeness, namely giving praise to the speech partner, which is often spoken by Udin.Keywords: representative, language politeness, film AbstrakRepresentatif Kesantunan Tokoh-Tokoh dalam Film The Fabulous Udin Karya Rons Irawan. Penelitian ini bertujuan untuk mengetahui dan memahami kesantunan dalam tindak tutur bahasa dari film The Fabulous Udin guna menjadi teladan bagi pembaca, sebab dalam film tersebut terdapat banyak adegan dan dialog yang patut diteladani. Penenlitian ini menggunakan metode deskriptif dan pendekatan kualitatif. Data pokok dalam penelitian ini yaitu tuturan yang menggambarkan kesantunan positif dan kesantunan negatif yang ditemukan dari film The Fabulous Udin sedangkan data penunjangnya adalah sinopsis film The Fabulous Udin. Representatif kesantunan tokoh-tokoh dalam film The Fabulous Udin karya Rons Irawan terbagi menjadi dua, yaitu kesantunan positif dan kesantunan negatif. Tindak kesantunan positif dan negatif dilakukan para tokoh guna kelancaran komunikasi serta menjaga harga diri penutur dan harga diri lawan bicara, sehingga terjalin kedekatan hubungan antara penutur dan mitra tutur. Kesantunan positif dalam Film The Fabulous Udin  adalah (1) memperhatikan apa yang sedang dibutuhkan mitra tutur, (2) menggunakan bentuk solidaritas kelompok, (3) melibatkan mitra tutur kedalam aktivitas penutur,  (4) menawarkan atau menjanjikan sesuatu, (5) memberikan pujian kepada mitra tutur,  (6) menghindari ketidakcocokan  dan (7) melucu. Adapun kesantunan negatif yang ditemukan dalam film The Fabulous Udin adalah (1) ungkapan secara tidak langsung, (2) bersikap pesimis, dan (3) meminimalkan paksaan.  Jenis kesantunan yang dominan adalah kesantunan positif yakni memberikan pujian kepada mitra tutur yang seringkali dituturkan oleh Udin.Kata Kunci: representatif,  kesantunan Bahasa, film